Functional characterization of endocytic signals in the SynDIG/PRRT family members SynDIG1 and SynDIG4 in heterologous cells and neurons - Speca, David J.; He, Chun-Wei; Meyer, Christina M.; Scott, Erin C.; Díaz, Elva (Frontiers in Cellular Neuroscience, 2025)
The transmembrane protein Synapse Differentiation Induced Gene 4 (SynDIG4), also known as Proline-rich transmembrane protein 1 (PRRT1), is an AMPA-type glutamate receptor (AMPAR) auxiliary factor that is necessary for maintaining extra-synaptic pools of GluA1. Loss of SynDIG4, and the subsequent decrease in extra-synaptic GluA1, has been found to significantly impact synaptic plasticity in the hippocampus. However, how SynDIG4 establishes and maintains these pools is unclear. Previous studies suggested that endocytic machinery is important for maintaining a pool of mobile surface AMPARs, and that proteins associated with such cellular machinery are critical for proper protein trafficking and internalization. Given that SynDIG4 co-localizes with GluA1 in early and recycling endosomes in cultured hippocampal neurons, we sought to identify the sorting signals that target SynDIG4 to endosomes to further elucidate the role of SynDIG4 in GluA1 trafficking. In this study, we report that SynDIG4 possesses a YxxΦ sorting motif, 178-YVPV-181, responsible for binding to the AP-2 complex cargo-sorting subunit μ2. This motif appears critical for proper SynDIG4 internalization, as SynDIG4 mutant 178-AVPA-181, which disrupts binding to μ2, induces aberrant SynDIG4 accumulation at the plasma-membrane of heterologous cells and primary rat hippocampal neurons. We also show that SynDIG4 mutants lacking an endocytic signal co-localize with GluA1 but less so with GluA2 on the surface of heterologous cells. Furthermore, we show that another family member, SynDIG1, is enriched in the trans-Golgi network (TGN) and can traffic between the TGN and plasma membrane. We have identified a non-canonical μ2 binding sequence in SynDIG1 that induces aberrant accumulation at the plasma membrane of heterologous cells and primary rat hippocampal neurons, suggesting a conserved role for μ2-mediated endocytosis within the SynDIG family. These results provide important insight into the mechanisms by which SynDIG proteins are targeted to endosomal compartments as a step in understanding SynDIG-mediated regulation of AMPAR trafficking.